2011
DOI: 10.1097/aco.0b013e328344587f
|View full text |Cite
|
Sign up to set email alerts
|

A speedy recovery: amphetamines and other therapeutics that might impact the recovery from brain injury

Abstract: Impairment after brain injury is reduced if adequate early treatment is established. On the basis of current findings amphetamine after brain injury cannot be recommended. In patients with an increased ICP the maintenance of an adequate cerebral perfusion pressure is required. In patients with increased ICP under controlled ventilation, the combination of ketamine with, for example, a short-acting benzodiazepine and opioid or methohexital is equally well tolerated. Ketamine decreases ICP without lowering blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Moreover, astroglial hemichannels were shown to contribute to amplification of inflammatory responses leading to neuronal damages (Bennett et al, ). Thus the inhibitory effects of propofol and ketamine on hemichannel activity in astrocytes may also contribute to their reported neuroprotective effects (Garnier and Bonnet, ; Harbeck‐Seu et al, ), and support the choice of ketamine and propofol for sedation and/or general anesthesia for patients with neuroinflammatory diseases.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, astroglial hemichannels were shown to contribute to amplification of inflammatory responses leading to neuronal damages (Bennett et al, ). Thus the inhibitory effects of propofol and ketamine on hemichannel activity in astrocytes may also contribute to their reported neuroprotective effects (Garnier and Bonnet, ; Harbeck‐Seu et al, ), and support the choice of ketamine and propofol for sedation and/or general anesthesia for patients with neuroinflammatory diseases.…”
Section: Discussionmentioning
confidence: 96%
“…While this early study is encouraging, other subsequent small stroke trials have not been as successful. A recent review analyzed ten clinical trials conducted on stroke patients using D-amphetamine and found that only two reported a significant improvement in neurological outcomes (Harbeck-Seu et al, 2011). Interestingly, adverse events were reported in three trials.…”
Section: Clinical Studiesmentioning
confidence: 97%